Work-related stress disorders: variability in clinical expression and pitfalls in psychiatric diagnosis - Buselli, Rodolfo; Veltri, Antonello; Baldanzi, Sigrid; Bozzi, Silvia; Marino, Riccardo; Chiumiento, Martina; Dell'Osso, Liliana; Cristaudo, Alfonso (La Medicina del Lavoro, 2016)
Background: Putative occupational stress-related psychiatric disorders are Adjustment Disorders (AD) and Post-Traumatic Stress Disorder (PTSD). Mood Disorders (MD) are not excluded but are unlikely to be identified as occupational diseases. The differential diagnosis between AD and MD is not easy and is based on strict categorical criteria. Objectives: The aim of this study  was to explore differences in personality and mood spectrum symptoms among workers investigated for occupational stress suffering from AD or MD. Methods: Sixty-two patients with AD and 43 with MD were recruited and evaluated by means of rating scales for psychosocial occupational risk and work-related stress (WHS, CDL, OSQ), for sleep disturbances (PSQI), for personality disorders (SCID-II) and for mood spectrum symptoms (MOODS-SR). Results: The diagnostic groups did not differ for WHS, OSQ and PSQI scores. The duration of exposure to stressful/adversative work situations was significantly higher in the MD group (p=0.03). Positive family psychiatric history (p=0.005), personality disorders (p=0.009) and pathological personality traits (p